Modern Architecture and the Evolution of Form, Space, and Society - Shawesh, Feeras (AlQalam Journal of Medical and Applied Sciences, 2025)
This study explores how modern architecture developed from the late 19th to the mid-20th century, focusing on the forces that reshaped how buildings were designed and experienced. It examines how new technologies, social change, and artistic movements together transformed architectural form and purpose. Through case studies and comparisons, the paper highlights major movements such as Bauhaus, De Stijl, and Soviet Constructivism, as well as adaptations in regions like the United States, Japan, and Egypt. By combining theory, history, and visual analysis, the research shows how modernism created a new architectural language, one based on function, material honesty, and social ideals. It also discusses how these ideas continue to influence contemporary design, education, and urban development.